PENERAPAN MODEL PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI SUDUT - Siti Patimah, Dewi; Effy Mulyasari; Shylvia Desty Gazella (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The researcher identified an issue occurring among third-grade students at a primary school in Bandung. The problem observed was a lack of achievement in mathematics, particularly in the topic of angles. To address this issue, the researcher implemented the project-based learning model. The research method used was Classroom Action Research (CAR), which involved conducting activities over three cycles. The results of the study indicate an improvement in students' learning outcomes in mathematics on the topic of angles. Specifically, the students' scores improved from 47.98 in the pre-cycle to 90.74 in the third cycle, reflecting an increase of 42.76 points, nearly doubling the previous learning outcomes.